Gross anatomy : dispatches from the front (and back) - Altman, Mara (G.P. Putnam's Sons, 2018)
A doodle-illustrated collection takes readers on an anecdotal tour of the female body that explores the social biases, self-maintenance practices, and aesthetic realities that shape how women view themselves.